Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1111/j.1365-2958.2006.05301.x
|View full text |Cite
|
Sign up to set email alerts
|

The type III effectors HsvG and HsvB of gall‐forming Pantoea agglomerans determine host specificity and function as transcriptional activators

Abstract: SummaryPantoea agglomerans pv. gypsophilae (Pag) elicits galls on gypsophila and a hypersensitive response on beet, whereas P. agglomerans pv. betae (Pab) induces galls on both beet and gypsophila. The pathogenicity of both pathovars is dependent on the presence of a plasmid harbouring type III secretion system (TTSS) components and effectors. The HsvG TTSS effectors of Pag (HsvG-Pag) and Pab (HsvGPab) determine the host specificity of both pathovars on gypsophila. Here we describe a novel HsvG homologue, HsvB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
67
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 50 publications
(76 reference statements)
0
67
0
Order By: Relevance
“…On: Sat, 12 May 2018 18:26:09 transcription (Nissan et al, 2006). Recent preliminary results demonstrated that also in planta HsvG and HsvB acted as TAL effectors in a host-specific manner (Nissan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…On: Sat, 12 May 2018 18:26:09 transcription (Nissan et al, 2006). Recent preliminary results demonstrated that also in planta HsvG and HsvB acted as TAL effectors in a host-specific manner (Nissan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Transient expression of GFP-HsvG or GFP-HsvB fusions in leaves of gypsophila, beet or melon (a non-host) showed that HsvG and HsvB localized to the nuclei of both host and non-host plants. By means of random binding-site selection (Okuno et al, 2001) and gel-shift assay, HsvG was demonstrated to be a double-stranded DNA-binding protein with a consensus DNA-binding site (Nissan et al, 2006). The localization inside the nucleus, on the one hand, and the DNA binding, on the other hand, led to the hypothesis that HsvG and HsvB act as transcription activator-like (TAL) effectors.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations